2010
DOI: 10.1111/j.1365-2958.2010.07122.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial degradation in acetic acid-induced yeast apoptosis: the role of Pep4 and the ADP/ATP carrier

Abstract: SummaryWe have previously shown that acetic acid activates a mitochondria-dependent death process in Saccharomyces cerevisiae and that the ADP/ATP carrier (AAC) is required for mitochondrial outer membrane permeabilization and cytochrome c release. Mitochondrial fragmentation and degradation have also been shown in response to this death stimulus. Herein, we show that autophagy is not active in cells undergoing acetic acid-induced apoptosis and is therefore not responsible for mitochondrial degradation. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 52 publications
16
105
3
3
Order By: Relevance
“…yca1-mtGFP cells showed a punctuated mitochondrial morphology at both times analysed, indicative of mitochondrial damage [55]. Similarly WT-mtGFP showed mitochondrial fragmentation as already reported [56][57]. Our results shows that, notwithstanding the lack of cyt c release in yca1 cell AA-PCD [16], mitochondrial fission occurs en route to both WT and yca1 cell AA-PCD pathways.…”
Section: Accepted Manuscriptsupporting
confidence: 78%
“…yca1-mtGFP cells showed a punctuated mitochondrial morphology at both times analysed, indicative of mitochondrial damage [55]. Similarly WT-mtGFP showed mitochondrial fragmentation as already reported [56][57]. Our results shows that, notwithstanding the lack of cyt c release in yca1 cell AA-PCD [16], mitochondrial fission occurs en route to both WT and yca1 cell AA-PCD pathways.…”
Section: Accepted Manuscriptsupporting
confidence: 78%
“…Release of lethal factors from mitochondria, such as cytochrome C, contributes to an apoptotic death process [78]. Moreover, following the induction of apoptosis, mitochondria are degraded, either through mitophagy [79] or by proteolysis through the Pep4 peptidase that is released from vacuoles at this stage [78]. Pep4 mediated proteolysis requires the presence of the mitochondrial ADP/ATP carrier (AAC) proteins, potentially to enable mitochondrial permeabilization.…”
Section: Metabolic Cross-talkmentioning
confidence: 99%
“…Upon prolonged growth in acetic acid, alterations in mitochondrial structure and function can occur which include reduction in cristae number, mitochondrial swelling, ROS accumulation, depolarization of the inner membrane and decreased respiration. Release of lethal factors from mitochondria, such as cytochrome C, contributes to an apoptotic death process [78]. Moreover, following the induction of apoptosis, mitochondria are degraded, either through mitophagy [79] or by proteolysis through the Pep4 peptidase that is released from vacuoles at this stage [78].…”
Section: Metabolic Cross-talkmentioning
confidence: 99%
“…However, more recent data demonstrated that these compartments are highly regulated and also have important functions in ion homeostasis, response to nutrient deprivation, osmotic and ionic stress, autophagy and even in cell death (Guicciardi et al, 2004;Klionsky et al, 1990;Li & Kane, 2009;Pereira et al, 2010;Schauer et al, 2009), supporting the view that vacuoles/lysosomes are highly sensitive and responsive to different cellular challenges, and not only storage or degradative compartments. Almost all vacuolar functions depend either on the acidic pH of the lumen or on the pH gradient across the membrane.…”
Section: Introductionmentioning
confidence: 97%